Martian Multichannel Diode Laser Spectrometer (M-DLS) for In-Situ Atmospheric Composition Measurements on Mars Onboard ExoMars-2022 Landing Platform - Alexander Rodin; Imant Vinogradov; Sergei Zenevich; Maxim Spiridonov; Iskander Gazizov; Viktor Kazakov; Viacheslav Meshcherinov; Ilya Golovin; Tatyana Kozlova; Yuri Lebedev; Svetlana Malashevich; Artem Nosov; et al. (Applied Sciences, 2020)
We present a concept of the Martian multichannel diode laser spectrometer (M-DLS) instrument, a part of the science payload onboard Kazachok landing platform in the framework of the ExoMars mission second stage. The instrument, a laser spectrometer operating in the mid-IR spectral range, is aimed at long-term monitoring of isotopic ratios in main Martian volatiles—carbon dioxide and water vapor—in the near-surface atmosphere. The M-DLS spectrometer utilizes the integrated cavity output spectroscopy (ICOS) technique to enhance an effective optical path length and combines high sensitivity and measurement accuracy with relatively simple and robust design. Provided proper compensation of systematic errors by data post-processing, retrievals of main isotopic ratios with relative accuracy of 1% to 3% are expected during at least one Martian year.